Rancang Bangun Tranformator Pit Untuk Runway Edge Light - Alba, Ahmad Al Baihaqi Husaini; Widiarto , Hendro; Soebiantoro , Rubby (Langit Biru: Jurnal Ilmiah Aviasi, 2023)
The AFL has an important role in flight safety at airports. Runway edge light is the main component of AFL that guides aircraft during takeoff or landing. However, several airports in Indonesia have experienced runway edge light failures due to damage to the series circuit. This damage is caused by interference from water, dust, and rodents that are not fully protected by pit transformers. This research aims to design and implement a new pit transformer as a solution. Using a three-level and six-stage R&D method, the pit transformer is made of 304 stainless steel with a thickness of 2 mm in a cylindrical shape and equipped with HDPE pipes to secure the series circuit from damage. Waterproof and functional tests were conducted in the laboratory. The results show that the pit transformer is able to protect series circuit components, optimize installation layout, and improve maintenance and repair efficiency. This research has the potential to strengthen the reliability of AFL series circuit systems and flight operations.